ANALISIS KERUGIAN DAN PEMETAAN SEBARAN SERANGAN RAYAP PADA BANGUNAN SEKOLAH DASAR NEGERI DI BAGIAN TIMUR KOTA PEKANBARU - Nico Christian; Yunus Afifuddin; Lutfhi Hakim (Peronema Forestry Science Journal, 2016)
Termites were one of the most important wood destroying organisms because of the damage caused by it was the largest compared with other wood destroying organism. One of the targets of termites attacks that were rarely investigated were school buildings. The purpose of this research was to get the amount of damage and economic losses caused by termites attacks on public elementary school buildings in the Pekanbaru city. The mapping of the distribution of termite attack by using a Geographic Information System (GIS). The method used in this research is purposive sampling which means directly choose the samples that were going to be selected as the subject of the research. From the result of the research, it was found that 100% of public elementary school buildings sampled attacked by termites with the percentage of 43,33% suffered moderate damage and 56,67% suffered minor damage. Keywords: Termites, School building, Economic losses.